Regional and Urban Column CO Trends and Anomalies as Observed by MOPITT Over 16 Years. Issue 5 (1st March 2021) - Hedelius, Jacob K.; Toon, Geoffrey C.; Buchholz, Rebecca R.; Iraci, Laura T.; Podolske, James R.; Roehl, Coleen M.; Wennberg, Paul O.; Worden, Helen M.; Wunch, Debra
Abstract: Atmospheric carbon monoxide (CO) concentrations have decreased since the beginning of the century, and the rate of decrease depends on the region. Depending on how regions are chosen, their boundaries may not always align with where there are differences in trends. To address this, we calculate trends within 0.4° × 0.4° grid cells independently throughout the globe using satellite CO retrievals from the Measurements Of Pollution In The Troposphere (MOPITT) satellite instrument from 2002 to 2017. These trends are found with the caveat that there are large singular biomass burning events somewhere nearly every year, and we include examples of large column CO anomalies during sporadic but large burning events in the North American and Eurasian boreal forests, the Amazon, Africa, and Indonesia. CO trends behave similarly within regions that span about a few thousand kilometers. Using TransCom region definitions, we find average trends between −0.9 and 0.1 ppb year −1 (about −0.9 to 0.1% year −1 ) for 2002–2017. Over 5‐year subsets, trends in TransCom regions vary between −3.6 and 1.8 ppb year −1 . This substantial spatial and temporal variability in trends is in agreement with other studies. With an understanding of regional trends, we compare with trends from urban areas. Generally, CO trends within urban areas are indistinguishable from regional trends. This may be because of a combination of noise in the data, the large footprint for MOPITT, or because anthropogenic CO reduction measures were implemented before the MOPITT record began. We provide case studies for a few cities, such as Los Angeles, and find long‐term variation in the rate of change of column CO. Plain Language Summary: Carbon monoxide (CO) is an atmospheric pollutant produced from combustion, such as wildfires and gasoline powered automobiles. We use a 16‐year satellite record to determine how atmospheric CO levels have been changing this century. Though sporadic, large wildfires happen somewhere every year which can affect trends in CO. We find trends for small regions (∼40 × 40 km) over the full 16 years and over 5‐year subsets. Trends vary significantly among regions and among the 5‐year subsets. We then examine how CO levels in cities change compared to their surrounding region. In most cases, CO trends in cities do not vary significantly from trends in the surrounding region. In some regions where we would expect a decrease (like Los Angeles and Mexico City), we find large intra‐annual variability. Key Points: Column CO (XCO ) trends vary regionally by 4%–5% year ‐1 on 5‐year scales with an overall global decrease Large CO emitting events can cause XCO anomalies of +20 ppb (∼20%) compared to other years over thousands of kilometer Urban trends are similar enough to regional trends that it is difficult to distinguish them with this system